Educação jurídica brasileira: entre as diretrizes curriculares nacionais e o Exame de Ordem - Nalesso, Thiago Fernando Cardoso (2021)
The work evaluates the effects of the National Curriculum Guidelines of the Ministry of Education (MEC) and the performance of the Brazilian Bar Association (OAB), through the National Commission for Legal Education and the Brazilian Bar Exam, on the quality of Brazilian legal education, with an emphasis on the curricular issues. Therefore, an analysis of the historical development and the political-ideological and epistemological foundation of Legal Courses in Brazil are carried out, followed by the description and interpretation of educational regulatory law and the emergence and development of the National Curriculum Guidelines. It was found that the Bar Exam, created to certify the minimum capacity to practice law, has become a tool for measuring the quality of legal education offered by higher education institutions in Brazil, in addition to being used as the main input for the granting of the “OAB Recomenda quality seal”. The use of the Bar Exam as a parameter for the quality of educational services, without proper methodological adequacy, influences a curricular standardization process with negative results in innovation, specialization, regionalization and flexibility of legal curricula, and, to a certain extent, it contradicts efforts made by the Legal Studies Commission of the Brazilian Bar. On the other hand, in the process of analysis and assessment, it was evinced the importance and the social need of the exam, that fulfills the function of protecting the rights and freedoms of citizens, which led to the conclusion of the need for adjustments in the evaluation methodology of the Bar Exam and the OAB quality seal, so that it can be more effective in achieving its purposes